International tax dispute resolution through mutual agreement procedure in Indonesia: Past, present, and future - Defi, Defi (Educoretax, 2024)
Mutual Agreement Procedure (MAP) is widely recognized as an international tax dispute resolution mechanism to resolve double taxation among jurisdictions, generally governed under Article 25 of double taxation agreements. To strengthen the effectiveness and efficiency of MAP, the Organisation for Economic Co-operation and Development (OECD) released the BEPS Action 14 report. To adapt to international best practices and peer-review recommendations, Indonesia, under the Directorate General of Taxes (DGT) Ministry of Finance of Indonesia, enacted several changes to its MAP domestic rules. This study aims to provide an analysis of developments of MAP regulations in Indonesia and to analyze its implementation to relieve double taxation and to adapt to both international best practices and international examinations through peer review in the Forum on Tax Administrations (FTA) on MAP. The author uses a doctrinal-empirical method with a historical approach with data set from 2016 to 2022. The findings indicate that Indonesia has had positive developments in its legal framework and practices in successfully concluding many MAP cases within the recommended time frame of 24 months. To enhance MAP in the future, DGT needs to deliver detailed guidance on multilateral MAP, to provide a secure transparent digitalized administration system to both treaty partners and taxpayers, and to be aware of MAP arbitration with the recent development of global consensus under Two-Pillar Solution.